2018
DOI: 10.4317/jced.55180
|View full text |Cite
|
Sign up to set email alerts
|

Anterior teeth root inclination prediction derived from digital models: A comparative study of plaster study casts and CBCT images

Abstract: BackgroundTo assess the accuracy of digital models generated using commercially available software to predict anterior teeth root inclination characteristics and compare the results to relevant data obtained from CBCT images.Material and MethodsFollowing sample size calculation and after application of inclusion and exclusion criteria, pre-treatment maxillary and mandibular plaster models and the corresponding CBCT scans of 31 patients attending a private orthodontic clinic were selected. The subjects were 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Ortho Insight 3D software (Motion View LLC, Chattanooga, Tennessee, USA) tries to predict the shape of tooth roots using standard tooth models [ 34 , 35 ]. Studies which investigated the accuracy of this approach report deviations of 9.2—22.5 degrees [ 34 ], respectively, 7.95 – 15.28 degrees [ 35 ] between the actual and the estimated root axis in mean. Despite having comparably poor accuracy, this tool is already implemented in a commercial software for quick calculation of dental root course based on a surface scan.…”
Section: Discussionmentioning
confidence: 99%
“…Ortho Insight 3D software (Motion View LLC, Chattanooga, Tennessee, USA) tries to predict the shape of tooth roots using standard tooth models [ 34 , 35 ]. Studies which investigated the accuracy of this approach report deviations of 9.2—22.5 degrees [ 34 ], respectively, 7.95 – 15.28 degrees [ 35 ] between the actual and the estimated root axis in mean. Despite having comparably poor accuracy, this tool is already implemented in a commercial software for quick calculation of dental root course based on a surface scan.…”
Section: Discussionmentioning
confidence: 99%
“…At present, we are aware of only one software company that markets such a tool. This has been evaluated in a previous study, which showed a large range of discrepancy in the angle between the actual and estimated roots, reaching almost 40° in extreme cases [8]. However, CBCT images were used to acquire root information; since crown and root lengths derived from CBCT images may not be accurate due to resolution issues and artefacts [2, 7, 16], testing the software would be more appropriate with data derived from natural teeth.…”
Section: Discussionmentioning
confidence: 99%
“…We computed the required sample size based on the requirement to detect a difference of 3° between the actual root angulation and that estimated by the software. We set the alpha level to 0.05, power to 80% and the standard deviation of the difference to 7°, based on a previous study [8]. These values resulted in a minimum sample size of 43 teeth; we included 55, based on availability (Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three points are selected on each arch to define and orient the occlusion plane to ensure that the digital model is in the right reference plane. 10…”
Section: Occlusion Adjustmentmentioning
confidence: 99%